2018
DOI: 10.1002/jcb.27884
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐proteasome system and ER stress in the brain of diabetic rats

Abstract: The ubiquitin‐proteasome system (UPS) has been implicated in the pathogenesis of many neurodegenerative diseases. Endoplasmic reticulum (ER) stress is shown to play a pathological role in the development of diabetes and its complications. Hence, the current study is aimed to investigate the role of UPS and ER stress in the cerebral cortex of diabetic rats and examine the therapeutic effect of 4‐phenylbutyric acid (4‐PBA), an ER stress inhibitor. Male Sprague‐Dawley rats were divided into three groups: control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
(128 reference statements)
0
16
0
Order By: Relevance
“…However, the Hrd1 protein expression under the ER stress in the brain remains unclear. It has been reported that the protein levels of Hrd1 in the cortex are decreased both in diabetic rats and in AD brain compared to the control group rat and non-AD subjects, and the brains of these diabetic rats and AD patients experienced ER stress (Kaneko et al, 2010 ; Shruthi et al, 2019 ). ER is involved in the processing and trafficking of amyloid precursor protein (APP); once in the ER, APP can generate Aβ due to the γ-secretases (Plácido et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Hrd1 protein expression under the ER stress in the brain remains unclear. It has been reported that the protein levels of Hrd1 in the cortex are decreased both in diabetic rats and in AD brain compared to the control group rat and non-AD subjects, and the brains of these diabetic rats and AD patients experienced ER stress (Kaneko et al, 2010 ; Shruthi et al, 2019 ). ER is involved in the processing and trafficking of amyloid precursor protein (APP); once in the ER, APP can generate Aβ due to the γ-secretases (Plácido et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57] The ability of 4PBA to reduce acellular capillary density is consistent with previous studies. 19,58 Differences in pericyte ghost densities between controls and experimental groups, as well as between 4PBA and non-4PBA-treated mice within the same group, increased in significance moving outward from the optic disc. The trends observed with respect to pericyte ghost and microvessel vessel density in GlcN-supplemented mice are very similar to those in STZ-injected and ApoE −/− :Ins2 +/Akita mice, suggesting that ER stress, even in the absence of hyperglycemia, may be a contributor to DR pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…74 In relation to diabetes, 4PBA has been found to improve diabetic encephalopathy and nephropathy, muscle atrophy, inflammation, and β-cell apoptosis. 58,[76][77][78][79][80][81] The reduction in CHOP expression with 4PBA suggests that 4PBA effectively alleviates ER stress to suppress the proapoptotic UPR. 68,82 Overall, this work characterizes the pathologic changes associated with DR in three different mouse models of diabetic atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations